Education, Taxation and Income Inequality: what Choices by the Median Voter? - Binet, Marie-Estelle; Delgay-Troise, Denis; Pentecôte, Jean-Sébastien (DEMO, 2020)
This study is following Meltzer and Richard (1981) on the link between inequality and redistribution studied within the median voter model. We propose an original theoretical framework with heterogeneous choices of qualification by active voters, following the idea put forward by Razin et alii (2002, 2004). We first show how the choice of qualification by the decisive voter directly influences his preferences in terms of income taxation, and vice versa. While a decrease in education costs increases the share of the educated population, its effect on redistribution is contrasted. Economies with similar education costs may choose high or low redistribution rates, despite high inequality. This partly invalidates Meltzer and Richard's result.(original abstract)